CLINICAL AND HORMONAL CHARACTERISTICS OF PATIENTS WITH POLYCYSTIC OVARY SYNDROME IN A PERUVIAN TERTIARY CENTER - Paz-Ibarra, Jose; Quintana-Pinto, Oscar (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES To describe the clinical and hormonal characteristics of patients with PCOS in a Peruvian center. METHODOLOGY Descriptive study that evaluated the clinical, biochemical and ultrasound characteristics of patients with PCOS at the Hospital Edgardo Rebagliati Martins, Lima-Peru in 2019. RESULTS We evaluated 100 consecutive patients, age range between 14 to 43 years (x ± SD: 27.2±7.3). Menarche at 12.2 ± 1.5 years. Oligomenorrhea that began during adolescence was present in 84%. The most frequent reason for consultation was oligomenorrhea, obesity and infertility (primary in 11 and secondary in 4 women), 21% had a history of abortions. Hirsutism (modified Ferriman-Gallwey Score >8), nodular-cystic acne, and androgynous alopecia were present in 89%, 44%, and 21%, respectively. LH and FSH concentrations (early follicular phase) were 8.9 ± 5.7 and 4.4 ± 2.4 IU/L, respectively; LH/FSH ratio >2 in 61%. The mean concentration of free testosterone: 2.8 ± 1.2 (0.6 to 6.5 pg/mL), 47% had values above the upper limit of our laboratory (>2.6 pg/mL). Androstenedione was from 0.20 to6.60 (mean value of 3.0 ± 1.1 ng/mL), 45% had values above the upper normal value of our laboratory (>2.7 ng/mL). On ultrasonography, 78% presented with the morphology of polycystic ovaries (follicular cysts >12, 2 – 9 mm in diameter, ovarian volume ≥10 mL); endometrial thickness >5 mm in 33%. CONCLUSION The most frequent reason for consultation was ovarian dysfunction, and hirsutism was the most prevalent clinical alteration. Hyperandrogenemia was present in 50% and polycystic morphology in 75%.